How Does Diversity Affect Team Cognitive Processes? Understanding the Cognitive Pathways Underlying the Diversity Dividend in Teams - Martins, Luis L.; Sohn, Wonbin (Academy of Management Annals, 2022)
The diversity literature has long proposed that diversity benefits team performance because the broader range of information, knowledge, and perspectives that members with different attributes brin...